Influence of Nano-SiO2 on the Consistency, Setting Time, Early-Age Strength, and Shrinkage of Composite Cement Pastes - Yu Chen; Yi-fan Deng; Meng-qiang Li (Advances in Materials Science and Engineering)
The study outlined the raw materials and mix proportions to prepare composite cement pastes with the addition of silica-based micro- and nanoparticles. The effects of amorphous nano-SiO2 on the early-age properties, including the consistency, setting time, early-age strength, and chemical and autogenous shrinkages, were investigated. Under the condition of the same dosage of superplasticizer used, the consistency of cement paste with nano-SiO2 is higher than that with silica fume. Significant reductions of the initial and final setting times are observed especially for nano-SiO2 addition groups, and the time difference between the initial and final setting times goes up with the increasing proportions of nano-SiO2. The addition of nano-SiO2 is more helpful to the improvement of early-age strengths of the paste with or without fly ash admixed than silica fume additive for the same mass proportion. Both the chemical and autogenous shrinkages of cement paste develop with the increasing amount of micro- or nanolevel silica particles; however, nano-SiO2 plays a more active role than silica fume in inspiring early-age shrinkage. The physical and chemical mechanisms of nano-SiO2 in cement paste are also discussed.